THE EFFECT OF AUDIT COMMITTEE AND AUDIT INDEPENDENCE ON THE QUALITY OF FINANCIAL STATEMENTS WITH AUDIT QUALITY AS A MODERATING VARIABLE - Much Rafi Dwi; Ruci Arizanda Rahayu (International Journal of Business, Law and Political Science, 2024)
General Background: The quality of financial statements is crucial for stakeholders to make informed decisions, and factors such as audit committees and audit independence play key roles in enhancing this quality. Specific Background: Previous studies have highlighted the importance of both an effective audit committee and independent auditing in maintaining the integrity of financial reporting. However, the extent to which these factors influence financial statement quality, especially in manufacturing firms in emerging markets, remains underexplored. Knowledge Gap: Additionally, the moderating role of audit quality, particularly from firms audited by Big Four firms, on the relationship between audit committees, audit independence, and financial statement quality has not been thoroughly examined. Aims: This study seeks to examine the impact of the audit committee and audit independence on the quality of financial statements, with audit quality as a moderating variable. Results: Based on a sample of 120 financial statements from manufacturing companies listed on the Indonesia Stock Exchange (IDX) between 2019 and 2023, this study found that both the audit committee and audit independence positively affect the quality of financial statements. However, audit quality does not moderate the effect of either the audit committee or audit independence on financial statement quality. Novelty: This research provides new insights into the limited role of audit quality as a moderating variable, suggesting that even audits by Big Four firms may not necessarily amplify the benefits of strong audit committees and audit independence. Implications: These findings imply that companies should focus on strengthening audit committee practices and enhancing auditor independence, regardless of whether they engage with Big Four auditors, to improve financial statement quality. Future research should explore additional variables that could influence or moderate this relationship.